Correction: Monitoring independence in daily life activities after trauma in humanitarian settings: Item reduction and assessment of content validity of the Activity Independence Measure-Trauma (AIM-T). - Bérangère Gohy; Christina H Opava; Johan von Schreeb; Rafael Van den Bergh; Aude Brus; Abed El Hamid Qaradaya; Jean-Marie Mafuko; Omar Al-Abbasi; Sophia Cherestal; Livia Fernandes; Andre Da Silva Frois; Eric Weerts; et al. (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0001334.].